Diversity of Insect Pests, Parasitoids, and Predators on Rice Plants (Oryza Sativa L.) in Minahasa Regency - Maxi Lengkong; Noni N. Wanta; Meisye H. B. Paruntu (Jurnal Penelitian Pendidikan IPA, 2026)
Rice (Oryza sativa L.) is one of the most important crops as a major source of carbohydrates for the majority of the world's population. However, to date, rice farming in West Kakas District, Minahasa Regency, still faces problems due to pest attacks. The purpose of this study was to determine the types and diversity of insects on rice plants in West Kakas District, Minahasa Regency. The research was conducted in West Kakas Subdistrict, which was determined using the purposive method, at four locations with five observation points. Insects were captured directly using insect nets. The captured insect samples were collected and grouped according to type. The types and population densities of the captured insects were counted and identified, then analyzed for diversity using the Shenon and Wivier formula to obtain the diversity index (H), similarity index (E), richness index (R), and dominance index (C). The results of the study show that there are insect pests and natural enemies (parasitoids and predators). The insect pests consist of 5 orders, 12 families, and 16 species, namely Dolycorus sp, Scotinopharasp., Stenodema sp, Leptocorisa sp, Paraecosmetus sp, Cofana spectra, Recilia sp., Nephotetix sp, Oxya sp. , Anacridium sp, Chilo sp, Parnara sp, Cnaphalocrocis sp. , Orseolia sp , Chlorops sp, and Phyllotretra sp. Meanwhile, natural enemies consist of 3 orders, 9 families, and 9 species, namely Cyrtohinus sp. , sp, Agryophylax sp. , Sepedon sp., Encarsia sp., Menochilus sp. , Ophionea sp. , Paederus sp., Sceliphron sp. and Agriocnemis sp. The results of the Shannon and Wiever diversity analysis are H' = 3.04 or a high diversity index, the richness index R = 4.67 or moderate criterion value, the evenness index E = 0.52 or moderate and unstable evenness index, and the dominance index C = 0.377 or low dominance.